2022
DOI: 10.2427/11183
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of methicillin resistant Staphylococcus aureus isolated from hospitals environments and patients in Northern Palestine

Abstract: BACKGROUND: Staphylococcus aureus (S. aureus) is considered one of the most common pathogen to humans. Infections caused by this mocroorganism can be acquired through both hospital and community settings. This study was carried out to investigate molecular characterization of MRSA strains isolated from the patients and their environment in two hospitals (Rafidia hospital and Thabet hospital) inNorthern Palestine, and to determine the clonal identity between these strains and their possible contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
0
1
Order By: Relevance
“…Moreover, one limitation of this study is that only mecA genes were thought of and that even though rare, future evaluations need to include the mecC gene. The prevalence in our study was higher than that reported by previous studies conducted in Gaza and the West Bank (56.3%, 29%, and 45%, respectively) except for one that reported a slightly higher prevalence (82.3%), which could be explained by the phenotypic detection method used (oxacillin discs) which is known to be less specific than molecular testing [ 20 , 21 , 22 , 23 , 37 ]. Our results are comparable to those reported in Jordan, Egypt, and Cyprus, where more than 50% of the invasive S. aureus isolates were methicillin-resistant [ 38 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Moreover, one limitation of this study is that only mecA genes were thought of and that even though rare, future evaluations need to include the mecC gene. The prevalence in our study was higher than that reported by previous studies conducted in Gaza and the West Bank (56.3%, 29%, and 45%, respectively) except for one that reported a slightly higher prevalence (82.3%), which could be explained by the phenotypic detection method used (oxacillin discs) which is known to be less specific than molecular testing [ 20 , 21 , 22 , 23 , 37 ]. Our results are comparable to those reported in Jordan, Egypt, and Cyprus, where more than 50% of the invasive S. aureus isolates were methicillin-resistant [ 38 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The highest rate of PVL among hospitals in the Gaza Strip was found in Al Naser and Al Aqsa hospitals (32.9% and 31.7% respectively). In comparison with previous studies that were conducted in Palestine, our results are consistent with those of two hospitals from the West Bank and East Jerusalem [23] (29.5%) but higher than those of Rafidia and Thabet hospitals (West Bank) [37] and from healthy children throughout the Gaza Strip [21] (14.3% and 8.5%, respectively). These differences in PVL prevalence could be a reflection of the different dominant MRSA clones circulating in these regions that may or may not harbor pvl genetic determinants.…”
Section: Discussionsupporting
confidence: 91%